Prospective study of platelet count as a prognostic marker in predicting feto-maternal outcome in gestational hypertension - Saisree, M. Jyothsna; Alluri, Shreya; Kameswaramma, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hypertensive disorders of pregnancy are one of the leading causes of maternal and neonatal morbidity and mortality worldwide. Hypertensive disorders of pregnancy (HDP) affects approximately 5-7% of all pregnancies. The reported incidence of HDP in India ranges from 5% to 15%. These disorders form a deadly triad-in conjunction with hemorrhage and infection, in significantly contributing to maternal morbidity and mortality. Objectives were to determine the correlation between the severity of HDP and low platelet count; to analyze maternal and fetal outcomes in relation to thrombocytopenia; to aid in early diagnosis and management and to prevent complications and thereby improving maternal and fetal outcomes. Methods: A hospital-based prospective study was conducted in women with a provisional diagnosis of gestational hypertension over a period of 18 months. The study group comprised of pregnant women who were more than 20 weeks and were subjected to detailed history: pre-obstetric history, family history, general physical examination, abdominal examination, routine laboratory investigations, and ultrasonography and Doppler. Results: In the study, platelet count at ≤275000 cut-offs had the highest sensitivity of 52.11%, specificity of 82.76%, PPV of 88.1%, and NPV of 41.4% in predicting feto maternal complications. Platelet count at ≤275000 cut-offs had the highest sensitivity of 62.86%, specificity of 69.23%, PPV of 52.4%, and NPV of 77.6% in predicting preeclampsia. Conclusions: From the study, it was concluded that in gestational hypertension the estimation of platelet count is thus a reliable method for early detection and management of hypertensive disorders of pregnancy. Platelet count was significantly decreased in subjects with maternal complications, fetal complications, and with respect to the severity of preeclampsia. Platelet count however had moderate validity in predicting fetomaternal complications.